2020
DOI: 10.1111/ejh.13384
|View full text |Cite
|
Sign up to set email alerts
|

MYC rearrangement and MYC/BCL2 double expression but not cell‐of‐origin predict prognosis in R‐CHOP treated diffuse large B‐cell lymphoma

Abstract: Objective Diffuse large B‐cell lymphoma (DLBCL) can be classified as germinal center B cell–like (GCB) or activated B cell–like (ABC)/non‐GCB based on cell‐of‐origin (COO) classification. This study evaluated the prognostic significance of COO classification in 250 patients diagnosed with de novo DLBCL who received R‐CHOP therapy. We also assessed whether the genomic status of MYC, BCL2, or MYC/BCL2 double expression (DE) could provide additional prognostic information for DLBCL patients. Methods The clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Hu et al and Green et al demonstrated that DE status was associated with a poor prognosis in both GCB and ABC/non-GCB-DLBCLs [12,13]. In contrast, other studies have reported that, despite the association between DE status and poor prognosis in GCB-DLBCLs, DE status could not predict survival in patients with ABC/non-GCB-DLBCLs [23,25,28]. These discrepancies might be attributed to differences in the methods used for COO classification among studies, characteristics of study populations, and the retrospective or prospective nature of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al and Green et al demonstrated that DE status was associated with a poor prognosis in both GCB and ABC/non-GCB-DLBCLs [12,13]. In contrast, other studies have reported that, despite the association between DE status and poor prognosis in GCB-DLBCLs, DE status could not predict survival in patients with ABC/non-GCB-DLBCLs [23,25,28]. These discrepancies might be attributed to differences in the methods used for COO classification among studies, characteristics of study populations, and the retrospective or prospective nature of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this, the prognostic significance of international prognostic index (IPI) was impaired and could only distinguish the low-risk with the high-risk group instead of the four risk groups as previously described (3)(4)(5). Alternatively, more and more clinical and biological markers were explored to predict the prognosis of DLBCL, including age, extranodal lesions, cell of origin, c-MYC and Bcl-2 co-expression or translocation, and different biochemical indicators (6)(7)(8)(9)(10)(11)(12)(13)(14). As the treatment developed, the prognostic values of these biochemical indicators may also change.…”
Section: Introductionmentioning
confidence: 99%
“…MYC is altered in many malignancies including lymphomas and some solid tumours 3 . Although the role of MYC dysregulation has been studied extensively in B‐cell lymphomas, 4–8 studies of MYC aberrations in T‐cell lymphomas are very limited. A few reports suggest that T‐cell lymphomas often have increased MYC copy number, but rarely carry MYC rearrangement ( MYC ‐R) 9‐12 .…”
Section: Figurementioning
confidence: 99%
“…3 In these situations, few data regarding management of the risk of relapse are available. 5,6 Our group proposed an intensive rituximab regimen inspired by the maintenance treatment of B-cell-indolent lymphoid malignancies. 7 We report here our experience with this strategy in iTTP patients who are unresponsive to standard pre-emptive rituximab treatment.…”
mentioning
confidence: 99%